2001
DOI: 10.1200/jco.2001.19.22.4209
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Tamoxifen and Aminoglutethimide Versus Tamoxifen Alone in the Adjuvant Treatment of Postmenopausal Breast Cancer Patients: Results of an Italian Cooperative Study

Abstract: Switching patients from tamoxifen to aminoglutethimide treatment resulted in comparable event-free survival, but longer overall survival was achieved in patients who were switched to aminoglutethimide as compared with those who continued to receive tamoxifen. Should these preliminary results be confirmed by larger studies with a similar design, which are now testing the effectiveness of the new, more active, and tolerable aromatase inhibitors, sequencing tamoxifen with an aromatase inhibitor could become a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 22 publications
1
38
0
2
Order By: Relevance
“…12 In the latest Italian study, cardiac toxicity was reported as cardiovascular disease; whereas, in the previous Italian trial, it was reported as cardiovascular events. 5,25 In the Intergroup Exemestane Study trial, events were defined as cardiovascular events (ie, ischemic cardiac; such as myocardial infarction and angina) plus other cardiac events, whereas only myocardial infarction was reported in the pooled analysis of ABCSG8 and ARNO. 10,13,26 Because of these and other differences across RCTs, any conclusion should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 In the latest Italian study, cardiac toxicity was reported as cardiovascular disease; whereas, in the previous Italian trial, it was reported as cardiovascular events. 5,25 In the Intergroup Exemestane Study trial, events were defined as cardiovascular events (ie, ischemic cardiac; such as myocardial infarction and angina) plus other cardiac events, whereas only myocardial infarction was reported in the pooled analysis of ABCSG8 and ARNO. 10,13,26 Because of these and other differences across RCTs, any conclusion should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11,12,26 Two trials were designed with the up-front strategy (11,108 patients), 8,9 and 5 trials were designed with the early switch strategy (8974 patients). 5,6,10,11,13,25,26 The median follow-up ranged from 28 months to 68 months. Trial characteristics are listed in Table 1.…”
Section: Selected Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio GROCTA 4B 23 , consistente en cirugía±RT±QT, seguido de tamoxifen 2-3 años, randomizado a tamoxifen 2-3 años frente a anastrozol 2-3 años. El número de pacientes incluidos ha sido de 448, con un seguimiento medio de 36 meses, recaída locorregional 13% en brazo tamoxifen frente a 2% en anastrozol, metástasis a distancia 19% frente a 10% y aparición de segundo primario, 10% frente a 5%.…”
Section: Ensayo Ibcsg VIIIunclassified
“…The benefit in mortality, favoring the switching strategy, was demonstrated by the first mature analysis of the former of the 2 studies performed by us in this framework. 14 The latter trial adopted the same design with anastrozole (ANA), a more potent aromatase inhibitor, in place of aminoglutethimide (AG). The preliminary analysis of this study showed a significant difference between groups in relation to both event-free and recurrence-free survival in favor of the women who switched to ANA.…”
mentioning
confidence: 99%